A Sociological Study of Married Female College Teacher: A Review Study - Minakshi Mili (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of this research paper is to critical review the existing literature on married female college teacher and explores its findings to develop a new insights and future directions for further research. This research paper has tried to display all the existing literature findings in a systematic way. Without knowing the past we cannot do something new in any field. If we want to do something new it is necessary to scan the past of the particular subject of the field and its related literature. Review of literature assists others for further research in this field.